Effects of electric field methods on modeling the midlatitude ionospheric electrodynamics and inner magnetosphere dynamics. Issue 5 (22nd May 2017) - Yu, Yiqun; Jordanova, Vania K.; Ridley, Aaron J.; Toth, Gabor; Heelis, Roderick
Abstract: We report a self‐consistent electric field coupling between the midlatitude ionospheric electrodynamics and inner magnetosphere dynamics represented in a kinetic ring current model. This implementation in the model features another self‐consistency in addition to its already existing self‐consistent magnetic field coupling with plasma. The model is therefore named as Ring current‐Atmosphere interaction Model with Self‐Consistent magnetic ( B ) and electric ( E ) fields, or RAM‐SCB‐E. With this new model, we explore, by comparing with previously employed empirical Weimer potential, the impact of using self‐consistent electric fields on the modeling of storm time global electric potential distribution, plasma sheet particle injection, and the subauroral polarization streams (SAPS) which heavily rely on the coupled interplay between the inner magnetosphere and midlatitude ionosphere. We find the following phenomena in the self‐consistent model: (1) The spatially localized enhancement of electric field is produced within 2.5 < L < 4 during geomagnetic active time in the dusk‐premidnight sector, with a similar dynamic penetration as found in statistical observations. (2) The electric potential contours show more substantial skewing toward the postmidnight than the Weimer potential, suggesting the resistance on the particles from directly injecting toward the low‐ L region. (3) The proton flux indeed indicates that the plasma sheet inner boundary at the dusk‐premidnight sector is located further away from the Earth than in the Weimer potential, and a "tongue" of low‐energy protons extends eastward toward the dawn, leading to the Harang reversal. (4) SAPS are reproduced in the subauroral region, and their magnitude and latitudinal width are in reasonable agreement with data. Key Points: Self‐consistent treatment of electric field now included in the kinetic ring current model RAM‐SCB‐E, advanced from previous empirical model Self‐consistent electric field reproduced observed dynamic spatial distribution of local electric field enhancement in the dusk sector Self‐consistent electric field method captured subauroral polarization streams (SAPS)